Synthesis and cytotoxic activity of per-acetylated and halogenated derivatives of nucleosides in breast cancer cells - JF Berrío Escobar; MH Pastrana Restrepo; E Galeano Jaramillo; DM Márquez Fernández; ME Márquez Fernández; A Martínez Martínez
ABSTRACT Objectives: To make the synthesis of halogenated derivatives on the nitrogenous base and their respective acyl ester and amide type derivatives for all hydroxyl and amine groups of the uridine and cytarabine nucleosides, and evaluate cytotoxicity against breast cancer cell line. Methods: First, it was accomplished the halogenation reaction on the 5-position of the nitrogenous base, subsequently, the ester and amide derivatives were performed for all hydroxyl and amine group present in the nucleosides. Besides, the uridine acetonide derivatives as prepared by acid catalysis. The products were characterized by nuclear magnetic resonance spectroscopy (1H RMN y 13C RMN) and mass spectrometry in positive mode by direct injection. Derivatives were evaluated in Chinese hamster ovary (CHO-K1) and human breast cancer (MCF-7) cell lines. Results: The four derivatives were obtained with chlorine and bromine for the uridine and cytarabine, respectively, their respective per-acetylated derivatives, the per-acetylated nucleoside and the uridine acetonide; the compounds were obtained with efficiency over 90%. The per-acetylated nucleosides and the halogenated and per-acetylated derivatives did not show inhibitory effects on cell viability in MCF-7 cell line. However, the per-acetylated and halogenated derivatives presented a higher cytotoxic activity than their respective per-acetylated nucleoside. The uridine 3',4'-acetonide showed a significant cytotoxicity on both cell lines. Conclusions: The per-acetylated nucleoside, and the respective halogenated derivatives with chlorine and bromine were obtained with high yields, nevertheless, these compounds did not exhibit a significant anti-proliferative activity (p<0.05), possibly due to a low intra-cellular activation.